54.3k views
5 votes
5(z+1) = 3(z+2) + 11Solve for Z

1 Answer

4 votes

This equation an eqaution with brackets with a simple variable z

We will first of all expand the brackets by multiplying through

The question states that,


\begin{gathered} 5(z+1)=3(z+2)+11 \\ By\text{ expanding the brackets we will have,} \\ 5z+5=3z+6+11 \\ 5z+5=3z+17 \\ By\text{ collecting like terms we will have} \\ \end{gathered}
\begin{gathered} 5z-3z=17-5 \\ 2z=12 \\ \text{divide both sides by 2} \\ (2x)/(2)=(12)/(2) \\ x=6 \end{gathered}

Hence,

The value of x = 6.

The correct answer is Option C

User Pfych
by
5.1k points